A new full‐scale testbed for structural health monitoring and soil–structure interaction studies: Kunming 48‐story office building in Yunnan province, China. Issue 7 (9th March 2020) - Todorovska, Maria I.; Niu, Ben; Lin, Guoliang; Cao, Changhu; Wang, Danling; Cui, Jianwen; Wang, Fangbo; Trifunac, Mihailo D.; Liang, Jianwen
Summary: This paper introduces a new and unique full‐scale testbed site for structural health monitoring and soil–structure system identification studies being developed in southwest China. The site is a 48‐story skyscraper with an extended four‐level basement, supported by piles, located in Kunming, the capital of Yunnan Province. Located in the diffused zone of collision of the Indian and Eurasian tectonic plates, Yunnan is one of the most active seismic areas in mainland China. The final sensor deployment will consist of 43 triaxial accelerometers (129 channels) and one weather station. The accelerometer array comprises (a) a structural array of 25 accelerometers installed at 10 levels aboveground, (b) a basement array of 14 accelerometers distributed in the first and fourth basements, and (c) two borehole arrays installed close to the basement perimeter wall, each with one accelerometers at the surface and another one at 50‐m depth, which is the depth reached by the piles. With such dense instrumentation of structure, basement, and pile foundation, this site will be the first permanently instrumented full‐scale testbed to enable identification of a soil‐foundation–basement‐structure system and validation of many assumptions commonly made in the prediction of the soil–structure interaction effects. A high‐performance wired local area network has been installed in the building, featuring a Precision Time Protocol‐enabled time synchronization and real‐time remote access over the Internet. The site will be fully operational in late spring of 2020. Results of preliminary system identification of the structure from ambient vibration test data are presented.